FIQIH VALUES FOR WOMEN IN THE BOOK I'ANATUNNISA BY MUHAMMAD USMAN - Istiyanti Nugraheni; Nurul Mubin; Ahmad Robihan (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
This study, entitled "The Values ​​of Women's Fiqh in Muhammad Usman's I'anatunnisa," aims to determine the values ​​of women's fiqh contained in Muhammad Usman's I'anatunnisa and its contents. The research used qualitative (literature) research. The data collection technique employed was literary literature. The data analysis technique employed was content analysis. Based on the results, it can be concluded that Muhammad Usman's I'anatunnisa deals with women's fiqh, discussing menstruation, istihadoh, and postpartum bleeding. The values ​​of women's fiqh contained in Muhammad Usman's I'anatunnisa include the honor of women's bodies and blood, health, the importance of maturity and responsibility, gender justice, the importance of education and knowledge, social and cultural context, and medical value